Distribution of Inheritance in the Perspective of Islamic Law: Analysis of the Procedures and Roles of Heirs - Zikri, Muhammad Zikri; Isnan, Muhammad Isnan (Cattleya Darmaya Fortuna, 2024)
The inheritance distribution system in Islamic law is regulated by clear and proportional provisions, aiming to ensure justice for all heirs. This distribution is based on the principle that each heir receives a portion according to their position and responsibilities in the family. However, in practice, the application of Islamic inheritance law often encounters challenges, such as disputes between heirs and inconsistencies between Islamic law and applicable positive law. In addition, restrictions on wills and differences in inheritance distribution between men and women are frequently debated issues. To overcome this problem, it is necessary to improve education on Islamic inheritance law, implement mediation as a solution to disputes, and make efforts to harmonize Islamic law with positive law so that inheritance distribution can be carried out fairly and in accordance with sharia principles.